Changes in the Structure of Wages in the 1980's: An Evaluation of Alternative Explanations - Bound, John; Johnson, George (American Economic Review, 1992)
During the 1980's, a period in which the average level of real wage rates was roughly stagnant, there were large changes in the structure of relative wages, most notably a huge increase in the relative wages of highly educated workers. This paper attempts to assess the power of several alternative explanations of the observed relative wage changes in the context of a theoretical framework that nests all of these explanations. Our conclusion is that their major cause was a shift in the skill structure of labor demand brought about by biased technological change.